Are wealthier times healthier in cities? Economic fluctuations and mortality in urban areas of Latin America - Leveau, Carlos Marcelo (2021)
Objective: To analyze the relationship between economic conditions and mortality in cities of Latin America. Methods: We analyzed data from 340 urban areas in ten countries: Argentina, Brazil, Chile, Colombia, Costa Rica, Guatemala, Mexico, Panama, Peru, and El Salvador. We used panel models adjusted for space‐invariant and time‐invariant factors to examine whether changes in area gross domestic product (GDP) per capita were associated with changes in mortality. Results: We find procyclical oscillations in mortality (i.e., higher mortality with higher GDP per capita) for total mortality, female population, populations of 0-9 and 45+ years, mortality due to cardiovascular diseases, malignant neoplasms, diabetes mellitus, respiratory infections and road traffic injuries. Homicides appear countercyclical, with higher levels at lower GDP per capita. Conclusions: Our results reveal large heterogeneity, but in our sample of cities, for certain population groups and causes of death, mortality oscillates procyclically, increasing when GDP per capita increases. In contrast we find few instances of countercyclical mortality.